Enhanced Ionic/Electronic Transport in Nano‐TiO2/Sheared CNT Composite Electrode for Na+ Insertion‐based Hybrid Ion‐Capacitors - Luo, Sainan; Yuan, Tao; Soule, Luke; Ruan, Jiafeng; Zhao, Yahui; Sun, Dalin; Yang, Junhe; Liu, Meilin; Zheng, Shiyou (Advanced functional materials, 2020)
Ion‐insertion capacitors show promise to bridge the gap between supercapacitors of high power densities and batteries of high energy densities. While research efforts have primarily focused on Li+‐based capacitors (LICs), Na+‐based capacitors (SICs) are theoretically cheaper and more sustainable. Owing to the larger size of Na+ compared to Li+, finding high‐rate anode materials for SICs has been challenging. Herein, an SIC anode architecture is reported consisting of TiO2 nanoparticles anchored on a sheared‐carbon nanotubes backbone (TiO2/SCNT). The SCNT architecture provides advantages over other carbon architectures commonly used, such as reduced graphene oxide and CNT. In a half‐cell, the TiO2/SCNT electrode shows a capacity of 267 mAh g−1 at a 1 C charge/discharge rate and a capacity of 136 mAh g−1 at 10 C while maintaining 87% of initial capacity over 1000 cycles. When combined with activated carbon (AC) in a full cell, an energy density and power density of 54.9 Wh kg−1 and 1410 W kg−1, respectively, are achieved while retaining a 90% capacity retention over 5000 cycles. The favorable rate capability, energy and power density, and durability of the electrode is attributed to the enhanced electronic and Na+ conductivity of the TiO2/SCNT architecture. This work presents a high‐performance 3D TiO2/sheared‐carbon nanotube (SCNT) anodic material for Na+‐based capacitors (SICs) using a framework that combines the benefits of reduced graphene oxide and CNTs to enable high rate capability and stability. The TiO2/SCNT composite anode is used in a SIC and exhibits gravimetric and volumetric power densities of 54.9 Wh kg–1 and 1410 W kg–1, respectively.